2022
DOI: 10.3389/fcimb.2022.999418
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of gut microbiota in cirrhotic patients with spontaneous bacterial peritonitis: A distinctive diagnostic feature

Abstract: BackgroundSpontaneous bacterial peritonitis (SBP) is a severe infection in cirrhotic patients that requires early diagnosis to improve the long-term outcome. Alterations in the gut microbiota have been shown to correlate with the development and progression of liver cirrhosis. However, the relationship between SBP and gut microbiota remains unknown.MethodsIn this study, we applied 16S rRNA pyrosequencing of feces to ascertain possible links between the gut microbiota and SBP. We recruited 30 SBP patients, 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…With a presence of intra-abdominal necrotic tissue in this model, the inflammation in the peritoneal cavity affects the balance of gut microbiota, despite the inflammatory lesions being walled off. Although these data are similar to the dysbiosis in several peritonitis models, such as spontaneous bacterial peritonitis, fecal peritonitis, and peritonitis in peritoneal dialysis [ 62 , 63 , 64 ], the dysbiosis in these situations might not be only from peritonitis alone but also from the underlying overt systemic responses, including cirrhosis, sepsis, and uremia, in these situations that might affect the gut dysbiosis. Here, despite the subtle systemic responses in the cecal ligation model, the alteration in fecal dysbiosis was prominent, supporting a vulnerability of the balance in microbiota in the gut to the microenvironment [ 65 ].…”
Section: Discussionsupporting
confidence: 56%
“…With a presence of intra-abdominal necrotic tissue in this model, the inflammation in the peritoneal cavity affects the balance of gut microbiota, despite the inflammatory lesions being walled off. Although these data are similar to the dysbiosis in several peritonitis models, such as spontaneous bacterial peritonitis, fecal peritonitis, and peritonitis in peritoneal dialysis [ 62 , 63 , 64 ], the dysbiosis in these situations might not be only from peritonitis alone but also from the underlying overt systemic responses, including cirrhosis, sepsis, and uremia, in these situations that might affect the gut dysbiosis. Here, despite the subtle systemic responses in the cecal ligation model, the alteration in fecal dysbiosis was prominent, supporting a vulnerability of the balance in microbiota in the gut to the microenvironment [ 65 ].…”
Section: Discussionsupporting
confidence: 56%
“…Our analysis results display that there are four common microbes in the top 20 ranking score lists from liver cirrhosis and epilepsy, i.e., Actinobacteria, Clostridia, Clostridiales and Klebsiella. It is reported that the relative abundances of Actinobacteria and Klebsiella both increase in patients with liver cirrhosis and epilepsy compared with healthy controls ( Chen et al, 2020 ; Lin et al, 2021 ; Dong et al, 2022 ; Zhou et al, 2022 ). Clostridiales with decreased abundance is strongly associated with the severity of liver cirrhosis and the seizure of epilepsy ( Zhang et al, 2018 ; Fukui, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Zhou et al demonstrated that patients with decompensated cirrhosis and SBP had a decreased microbial richness and increased microbial diversity [ 86 ]. Moreover, they found a different microbiota profile in patients with SBP compared with those without SBP, defined by an increase of 15 species including pathogens such as Klebsiella pneumoniae , Serratia marcescens and Prevotella oris and a decrease of some beneficial bacterial taxa, such as Faecalibacterium prausnitzii , Methanobrevibacter smithii and Lactobacillus reuteri [ 86 ]. Other studies revealed that Enterobacteriaceae are the most commonly translocated microbes identified in ascitic fluid of cirrhotic patients, and a higher proportion of Gram-negative bacteria in their gut microbiome was pointed out as the cause of SBP [ 8 ].…”
Section: Liver and Gut Microbiotamentioning
confidence: 99%
“…Therefore, these findings suggest that K. pneumoniae may translocate from the intestine to cause SBP. In cirrhotic patients with SBP, the abundance of the beneficial bacteria Faecalibacterium prausnitzii is negatively correlated with white blood cell count (WBC), C-reactive protein (CRP), procalcitonin (PCT) and Child–Turcotte–Pugh (CTP) score, while the abundance of E. coli was positively correlated with WBC, CTP score and Mayo End stage Liver Disease (MELD) score [ 86 ].…”
Section: Liver and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation